Why did schistosomiasis disappear from the southern part of the Eastern Cape? - Chris Appleton; Inbarani Naidoo (South African Journal of Science)
We reviewed the early literature and maps of the occurrence of urogenital schistosomiasis (bilharzia) in the Eastern Cape, South Africa from the 1860s until its decline from about 1900 and reappearance in 2002. Although this decline in transmission has received little attention to date, clinical descriptions of the disease over this period indicate that infection was common, probably patchy, although sometimes with severe morbidity. The long period of quiescence between 1900 and 2002 is thought to be as a result of several factors, but primarily because of the impact of the area's cold winters and drought-prone climate on the survival and reproduction of both the snail intermediate host Bulinus africanus and the intramolluscan stages of the parasite. The concept of an outbreak area is invoked to describe the occurrence of intense urogenital schistosomiasis transmission in localised areas for relatively short periods of up to 35 years in this the southernmost part of its range in Africa, a suboptimal environment for transmission.